Design and Build a Tour & Travel Applicationweb-Based Use Waterfall Method - Andronias Siregar; Arief Satriansyah; Rachmat Hidayat; Regel Miki Praditya (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2022)
Design and Build a Web-Based Tour & Travel Application is an application system that helps make it easier for users to process in booking Tour & Travel tickets. This Web-Based Tour & Travel Application System can be accessed by anyone, anywhere, and anytime as long as there is an internet network. Web-Based Tour & Travel Application System is an application built to improve services or services and promotional media for regional tours, making it easier for customers to book tour packages via the internet. This Web-Based Tour & Travel application was created using PHP and MySQL programming languages, and the method used to develop this system is the waterfall method, namely analysis, program design, code and test. With this, Design and Build a Tour & Travel Application can help introduce something or promote the development of a good tourist attraction so that many people are interested in coming to the attraction in the hope that it can help boost other sectors, such as: tourist visits, creative economy, opening up job opportunities, reducing unemployment.